Clinical phenotypes and associated factors in knee osteoarthritis in an African black population - Charles Sougué; Malick Diallo; Yannick Laurent Tchenadoyo Bayala; Ismaël Ayouba Tinni; Fulgence Kaboré; Wendlassida Joelle Stéphanie Zabsonré Tiendrebeogo; Patrick Wendpouiré Hamed Dakouré; Dieu-Donné Ouedraogo (Osteoarthritis and Cartilage Open)
Objective: Our objective was to study the clinical phenotypes of knee osteoarthritis in rheumatology in a black sub-Saharan African population. Methods: This study took place from October 1, 2022, to September 30, 2023, in the rheumatology department. It involved adult patients with knee osteoarthritis. The researchers used K-means clustering analysis to identify different phenotypes and logistic regression to determine associated factors. Results: A total of 321 patients were included in the study. The mean age was 58.7 years (ranging from 21 to 92 years), with a sex ratio of 0.23 (M/F). The study identified five clinical phenotypes through clustering: 152 patients (47.3 ​%) exhibited the “osteoporotic” phenotype, 113 patients (35.2 ​%) exhibited the “metabolic” phenotype, 17 patients (5.3 ​%) exhibited the “genetic” phenotype, 24 patients (7.4 ​%) exhibited the “biomechanical” phenotype, and 15 patients (4.6 ​%) exhibited the “post-traumatic” phenotype. The “osteoporotic” phenotype was significantly more frequent in patients aged 60 years or older (OR ​= ​1.13 [1.10; 1.16], p ​< ​0.0001) and in women (OR ​= ​2.44 [1.20; 4.94], p ​< ​0.0001). On the other hand, the “post-traumatic” phenotype was significantly more frequent in patients younger than 60 years (OR ​= ​1.93 [1.91; 1.96], p ​< ​0.0001) and in those with tibiofemoral osteoarthritis (OR ​= ​0.44 [0.21; 0.94], p ​= ​0.034). Conclusion: The osteoporotic and metabolic phenotypes were the most frequently observed. The osteoporotic phenotype was more common in women and patients over 60 years while the post-traumatic phenotype was more prevalent in tibiofemoral osteoarthritis under 60 years.